Pengaruh Financial Technology (Fintech) Terhadap Efektivitas Manajemen Keuangan Pada Pelaku Usaha Mikro Kecil Dan Menengah (Umkm) - Andini Andini; Alamanda Rajwa Shafira; Allena Angraini (Jurnal Ekonomi Manajemen Akuntansi Keuangan Bisnis Digital, 2026)
The rapid development of digital technology has encouraged the emergence of various innovations in the financial sector, one of which is Financial Technology (Fintech). The presence of fintech provides convenience for Micro, Small, and Medium Enterprises (MSMEs) in conducting transactions, managing finances, making digital payments, and accessing business financing. This study aims to analyze the effect of Financial Technology (Fintech) on the effectiveness of financial management among MSME actors. The research method used is a quantitative method with a survey approach. Data were obtained through questionnaires distributed to MSME actors who use fintech services in their business activities. Data analysis techniques were carried out using descriptive analysis and simple regression analysis to determine the relationship between fintech usage and the effectiveness of financial management. The results of the study indicate that the use of fintech has a positive effect on the effectiveness of MSME financial management. The utilization of fintech helps business actors manage cash flow, improve transaction efficiency, simplify financial recording, and expand access to financial services more quickly and practically. In addition, the use of digital financial technology also helps increase the productivity and competitiveness of MSMEs in the digital economic era. Therefore, fintech can be one of the strategic solutions in supporting more effective and efficient financial management for MSMEs.